2013
DOI: 10.3126/jaim.v2i1.7636
|View full text |Cite
|
Sign up to set email alerts
|

Young Ischemic Stroke in South Asia: A review

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Moreover, stroke incidence in the younger population has increased globally, with higher consequences physically, psychologically, and socially. Furthermore, other varying risk factors, such as air pollution, obesity, physical inactivity, alcohol consumption, and dyslipidemia, have also increased in the younger population 11–13 . In addition to the younger average age of stroke onset and higher incidence rates, the shift had also changed toward hemorrhagic stroke, which has higher fatality and disability, leading to DALY loss rates up to more than 10‐fold higher than the least affected countries 14 .…”
Section: Stroke Epidemiology In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stroke incidence in the younger population has increased globally, with higher consequences physically, psychologically, and socially. Furthermore, other varying risk factors, such as air pollution, obesity, physical inactivity, alcohol consumption, and dyslipidemia, have also increased in the younger population 11–13 . In addition to the younger average age of stroke onset and higher incidence rates, the shift had also changed toward hemorrhagic stroke, which has higher fatality and disability, leading to DALY loss rates up to more than 10‐fold higher than the least affected countries 14 .…”
Section: Stroke Epidemiology In Asiamentioning
confidence: 99%
“…Furthermore, other varying risk factors, such as air pollution, obesity, physical inactivity, alcohol consumption, and dyslipidemia, have also increased in the younger population. [11][12][13] In addition to the younger average age of stroke onset and higher incidence rates, the shift had also changed toward hemorrhagic stroke, which has higher fatality and disability, leading to DALY loss rates up to more than 10-fold higher than the least affected countries. 14 The prevalence of stroke, its risk factors, disability-adjusted life year (DALY), and mortality rate of HOPE Asia Network Countries are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, several studies have shown an increase in the number of young stroke patients. However, reports from developing and underdeveloped countries relating to young patients with stroke have been less frequent and were concerned with the higher frequency of undetermined causes of stroke [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current prevalence estimates for stroke in US younger adults are 0.6% (18-44) and 3.1% (45-64) [6]. The rates of stroke in younger populations may be even higher in developing countries [7].…”
Section: Introductionmentioning
confidence: 99%